Tuesday

October 21, 2014

October 21, 2014

Posted by **Ryan** on Monday, January 16, 2012 at 9:14am.

- math -
**drwls**, Monday, January 16, 2012 at 10:16amLet's first write that out as an equation.

P(x) = 2x^4 -3x^3 +5x^2 -1.

P(-4) = 2*256 -3*(-64) +5*16 -1

= 783

**Answer this Question**

**Related Questions**

math - What is P(-4) given that P(x) = 2x to the fourth power - 3x to the third ...

math - What is P(-4) given that P(x) = 2x to the fourth power - 3x to the third ...

math - What is P(-4) given that P(x) = 2x to the fourth power - 3x to the third ...

math - 1. unite similar terms with parenthesis. x=2 y=-3 and z=5 find the value ...

Algebra - I am so confused with the rules of exponents. I know them, but I have ...

Math 8R - Help!!!!!!!! - The expression 2(8a to the 2nd power + a - 1) + 3(a + 3...

Algebra - Factor each of following expressions x (4th power) - x (3rd power) - ...

Algebra - I'm not sure if anyone saw my question yesterday, but here it is again...

math - The question that have is to simplify and write the answer in ...

Math/Standard and scientific notation - Express each measure in standard form. (...